2011
DOI: 10.1021/bc200090x
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde PEGylation Kinetics: A Standard Protein versus a Pharmaceutically Relevant Single Chain Variable Fragment

Abstract: The mPEG-aldehyde PEGylation with two different PEG sizes and two proteins was experimentally determined with respect to yield, conversion, and selectivity. The kinetic behavior of these PEGylation reactions was simulated using a numerically solved set of differential equations. We show that the assumption of an inactivation of mPEG-aldehyde is crucial for the simulation of the overall PEGylation and that the inactivation is pH-dependent. We further demonstrate that ideal PEGylation parameters such as pH, temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 30 publications
5
33
0
1
Order By: Relevance
“…The high reactivity of the functionalized PEG goes in fact along with the hydrolysis of its active moiety which cannot be neglected. Moosmann et al (Moosmann et al, 2011) showed that accurate simulations are not possible without considering this deactivation reaction. Esters hydrolysis mechanisms have been thoroughly investigated over the years and appear to be pH-dependent, affected by both basic and acidic conditions (Day and Ingold, 1941).…”
Section: Kinetic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The high reactivity of the functionalized PEG goes in fact along with the hydrolysis of its active moiety which cannot be neglected. Moosmann et al (Moosmann et al, 2011) showed that accurate simulations are not possible without considering this deactivation reaction. Esters hydrolysis mechanisms have been thoroughly investigated over the years and appear to be pH-dependent, affected by both basic and acidic conditions (Day and Ingold, 1941).…”
Section: Kinetic Modelmentioning
confidence: 99%
“…Their kinetic model is easy to implement and represents an effective tool to simulate the formation of PEGylated proteins at various degrees of PEGylation (also named PEGamers). This model has already been used with some success 3 in the literature (Molek, 2008;Moosmann et al, 2011;Wang et al, 2014). The main limitation of the approach proposed by Laura et al is that the employed kinetic model does not allow the distinction between the various positional isomers that compose PEGamers of a given degree of PEGylation (doP).…”
Section: Introductionmentioning
confidence: 99%
“…The in vivo half-life of this pharmaceutically relevant target protein, used in this study, was increased by the covalent coupling of polyethylene glycol polymer chains (PEGylation) previously described by Moosmann et al (2011Moosmann et al ( , 2012. Like the parental chimeric (mouse/human) monoclonal IgG1 antibody Cetuximab, which is an FDA approved pharmaceutical drug, the humanized scFv is a competitive antagonist for EGF, which could be used in the treatment of metastatic colorectal cancer (Vincenzi et al, 2008;Boder and Jiang, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The lysine residues on the external surface of lactoferrin can be used to covalently couple molecules [19][20][21][22] [24][25][26].…”
mentioning
confidence: 99%